VARIABILITY OF COMBINING ABILITY IN DURUM WHEAT DEPENDING ON GROWTH CONDITIONS - V. S. Yusov; M. G. Evdokimov; B. M. Tatina (Вавиловский журнал генетики и селекции, 2014)
The variability of combining ability depending on growing conditions was studied in spring durum wheat varieties in a topcross system. It was found that the manifestation of the traits under study was determined by additive effects of genes and general combination ability variances were most susceptible to environmental conditions.